Knowledge and Practice on Emergency Contraceptive Pills Among Non-Health Bachelor Level Female Students in Kathmandu - Khatiwada, Sinju; Bhattarai, Amisha; Bist, Amrit (Clinical Medicine And Health Research Journal, 2023)
Introduction: Emergency contraception (ECPs) is hormonal contraception that is used within 72 to 120 hours after unprotected and unsafe sexual intercourse for the prevention of unintended pregnancies. It is important to prevent unwanted pregnancy and there by induced abortion. This study aimed to evaluate the knowledge and practice on ECPs among non-health bachelor level female students in Kathmandu. Methodology: This was a descriptive cross-sectional study of 388 female respondents at non-health bachelor colleges in Kathmandu, Nepal. Simple random sampling technique was used. Pre-tested self-administered questionnaire were used for data collection. Result: The study analyzed the knowledge levels of the study participants, finding that 55.15% had adequate knowledge, while 44.84% had inadequate knowledge. 21.64% practiced ECPs. The study also found a significant association (p value= 0.04) between knowledge level and ECPs practice. Conclusion: The study found that most respondents had adequate knowledge and a significant prevalence of ECP use in Kathmandu district. It is suggested that ECPs not intended to be used as regular form of contraception and should only be used in emergency situation. Frequent use can lead to irregular menstrual cycle and hormonal imbalances.